2014
DOI: 10.3109/09593985.2014.900835
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity and reliability of the Simple Goniometer iPhone app compared with the Universal Goniometer

Abstract: Objectives: The aim of this study was to assess the concurrent validity and reliability of the Simple Goniometer iPhone® app compared to the Universal Goniometer.Design: Within subject comparison design comparing the Universal Goniometer with the Simple Goniometer app.Setting: James Cook University, Townsville, Queensland, Australia.Participants: Thirty-six volunteer participants, with a mean age of 60.6 years (SD 6.2). Interventions: Not applicable.Main Outcome measure: Thirty-six participants performed three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
4
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 9 publications
3
73
4
10
Order By: Relevance
“…al were comparing iOS apps "GetMyROM" and "DrGoniometer" and found both reliable and comparable to the mechanical goniometer [13]. In another study testing the iOS accelerometer "Simple Goniometer", Jones et al judged the app reliable [14]. The four clinical studies support the results of this study with regard to the apps "DrGoniometer", GetMyROM" and "Simple Goniometer".…”
Section: Discussionsupporting
confidence: 66%
“…al were comparing iOS apps "GetMyROM" and "DrGoniometer" and found both reliable and comparable to the mechanical goniometer [13]. In another study testing the iOS accelerometer "Simple Goniometer", Jones et al judged the app reliable [14]. The four clinical studies support the results of this study with regard to the apps "DrGoniometer", GetMyROM" and "Simple Goniometer".…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the thoracic spine has multiple adjacent joints and its motion requires contraction of multi-joint musculature. It has been proposed that such characteristics are likely to reduce the reliability and hence validity for measurements of these joints which provides an explanation for why our validity data, while demonstrating a strong positive correlation (r = 0.835, P<0.001), was slightly lower in comparison to the majority of studies reviewed (Jones, 2014;Milanese, 2014;Mitchell, 2014;Norkin, 2016;Shin, 2012).…”
Section: Concurrent Valititycontrasting
confidence: 50%
“…Several of these articles used clinical tools as the gold standard reference (goniometer, inclinometer, scoliometer etc.) (Jenny et al 2016;Jones et al 2014;Tousignant-Laflamme et al 2013), however no study was identified that utilized a mobile phone application to determine thoracic spine rotation ROM (reliability or Validity).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the measurement of the mobile application was slightly more accurate than that obtained from UG, with no statistically significant differences between the measurements made by the students and those of the experienced physicians (ICC > 0,96 in both cases). In a similar study, Jones [20] carry out a comparison between UG and an iPhone app for measuring the passive flexion of the knee in a cohort of 36 subjects, no finding statistically On the basis of a cohort of five subjects, Ockendon and Gilbert [21] compare the validity of a purpose-built mobile application to that of a traditional goniometer for measuring knee range of motion. This results show that the values obtained from both measurement instruments are closely correlated, albeit with slight differences in favor of the mobile app (inter-observer correlation: was 0,994 vs. 0,952 and intraobserver correlation: was 0,982 vs. 0,927); the mean difference between the two is only -0,4º.…”
Section: Discussionmentioning
confidence: 99%